2015
DOI: 10.1161/hypertensionaha.114.04760
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nuclear Factor Erythroid 2–Related Factor 2 Coordinates Dimethylarginine Dimethylaminohydrolase/PPAR-γ/Endothelial Nitric Oxide Synthase Pathways That Enhance Nitric Oxide Generation in Human Glomerular Endothelial Cells

Abstract: Dimethylarginine dimethylaminohydrolase (DDAH) degrades (ADMA) which inhibits nitric oxide synthase (NOS). Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcriptional factor that binds to antioxidant response elements (ARE) and transcribes many antioxidant genes. Since the promoters of the human DDAH-1 and -2, eNOS and PPAR- γ genes contain 2–3 putative AREs, we hypothesized that they were regulated by Nrf2/ARE. Incubation of human renal glomerular endothelial cells (HRGECs) with the Nrf2 activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…There were significant correlations between Nrf2 and PPAR-γ, as well as the individual NOS isoforms, despite the unchanged gene transcriptions, which suggests the regulatory role of Nrf2 in NOS expressions in the heart and aorta; this mechanism remained unaltered by Epi. The coordinating role of Nrf2 in PPAR-γ expressions and endothelial NO generation was previously found by Luo et al [66]. Regarding Epi effects, relatively few in vivo and in vitro studies have investigated the genomic and proteomic effects of purified Epi, especially the expressions of the genes that were investigated in this study.…”
Section: Discussionsupporting
confidence: 59%
“…There were significant correlations between Nrf2 and PPAR-γ, as well as the individual NOS isoforms, despite the unchanged gene transcriptions, which suggests the regulatory role of Nrf2 in NOS expressions in the heart and aorta; this mechanism remained unaltered by Epi. The coordinating role of Nrf2 in PPAR-γ expressions and endothelial NO generation was previously found by Luo et al [66]. Regarding Epi effects, relatively few in vivo and in vitro studies have investigated the genomic and proteomic effects of purified Epi, especially the expressions of the genes that were investigated in this study.…”
Section: Discussionsupporting
confidence: 59%
“…PPARc agonists up-regulate Nrf2, and knockdown of PPAR-c reduced the mRNA expression for Nrf2 [46]. This indicates a tight, positive, twoway reinforcing transcriptional interaction between PPAR-c and Nrf2 that may improve endothelial function [46]. The interaction of PPARc with Nrf2 following ICH was illustrated in Figure 3.…”
Section: Peroxisome Proliferator-activated Receptor-c (Ppar-c)mentioning
confidence: 96%
“…Expression of Nrf2 was reduced by knockdown of PPAR-c, whereas PPAR-c was reduced by knockdown of Nrf2, thereby demonstrating two-way positive interactions. PPARc agonists up-regulate Nrf2, and knockdown of PPAR-c reduced the mRNA expression for Nrf2 [46]. This indicates a tight, positive, twoway reinforcing transcriptional interaction between PPAR-c and Nrf2 that may improve endothelial function [46].…”
Section: Peroxisome Proliferator-activated Receptor-c (Ppar-c)mentioning
confidence: 97%
“…The cysteine disulfide bridges in oxidized proteins were reduced by Trx system 32 . It was found that PPARγ could up-regulate Nrf2 33 34 . Our previous study had found that Tau protected against As 2 O 3 -induced autophagy in pancreas of rat offsprings through Nrf2/Trx pathway 35 .…”
mentioning
confidence: 99%